1969
DOI: 10.1017/s0003356100026830
|View full text |Cite
|
Sign up to set email alerts
|

The effect of level of feed intake in pregnancy and in lactation upon the productivity of sows

Abstract: SUMMARYEight research and teaching centres have co-operated in an experiment involving 132 sows. Six treatments were used, combining three levels of feeding in pregnancy with two in lactation. Pregnancy treatments were High 3−2 kg meal/day, Medium 2·4 kg/day and Low 1·6 kg/day; in lactation either a high level, 4·1 kg plus 0·2 kg/pig (h) or a medium level, 2·3 kg plus 0·2 kg/pig (m) were given. The sows were maintained on the same nutritional regime for three parities although inevitably some sows were lost be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

1971
1971
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 4 publications
6
18
0
Order By: Relevance
“…These changes in LW were greater in gilts than in older sows, which is in agreement with earlier results (Elsley, Bannerman, Bathurst, Bracewell, Cunningham, Dodsworth, Dodds, Forbes and Laird, 1969;Lee and Close, 1988). These changes in LW were greater in gilts than in older sows, which is in agreement with earlier results (Elsley, Bannerman, Bathurst, Bracewell, Cunningham, Dodsworth, Dodds, Forbes and Laird, 1969;Lee and Close, 1988).…”
Section: Discussionsupporting
confidence: 92%
“…These changes in LW were greater in gilts than in older sows, which is in agreement with earlier results (Elsley, Bannerman, Bathurst, Bracewell, Cunningham, Dodsworth, Dodds, Forbes and Laird, 1969;Lee and Close, 1988). These changes in LW were greater in gilts than in older sows, which is in agreement with earlier results (Elsley, Bannerman, Bathurst, Bracewell, Cunningham, Dodsworth, Dodds, Forbes and Laird, 1969;Lee and Close, 1988).…”
Section: Discussionsupporting
confidence: 92%
“…Apparently sows fed Lo compensated for their greater weight loss during Lac 1 [indicated by the differences (P<.01) in Lac 1 sow weaning weight]. Previous reports indicate that energy intake (Elsley et al, 1968;Adam and Shearer, 1975;O'Grady et al, 1975) and feed intake (Lodge et al, 1961;Elsley et al, 1969;Hitchcock et al, 1971) during lactation had no effect on net sow weight change during gestation. However, MacPherson et al (1969) and O'Grady (1971) reported that sows fed low protein diets during lactation tended to compensate by gaining more weight during the following gestation than those fed higher protein diets.…”
Section: Resultsmentioning
confidence: 94%
“…Farrowing rate (i.e., number of sows farrowed/number mated) was not significantly affected by energy intake during Lac 1. Although farrowing rate was not reported, Lidvall and Griffin (1962), Elsley et al (1969), Hitchcock et al (1971) and Varley and Cole (1976) reported that lactation feeding level had no influence on conception rate of sows. Similarly, energy intake during Lac 1 had no significant influence on the total number of fully developed pigs born or born alive; however, sows fed Lo farrowed lighter weight (P<.10) pigs than those fed Hi.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of documented for sows lactating for 6 to 8 adjustments to food intake will be modified weeks (Elsley, Bannerman, Bathhurst, by initial reserves of body lipid (Whittemore, Bracewell, Cunningham, Dodsworth, Dodds, Franklin and Pearce, 1980) which will depend Forbes and Laird, 1969;O'Grady, Elsley, to some extent on live weight at first mating. The effects of documented for sows lactating for 6 to 8 adjustments to food intake will be modified weeks (Elsley, Bannerman, Bathhurst, by initial reserves of body lipid (Whittemore, Bracewell, Cunningham, Dodsworth, Dodds, Franklin and Pearce, 1980) which will depend Forbes and Laird, 1969;O'Grady, Elsley, to some extent on live weight at first mating.…”
Section: Introductionmentioning
confidence: 99%